(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
griculture is one of India’s most vital sectors, and it is critical for the country’s economic survival and prosperity. Agriculture is the source of livelihood for around 70% of households and 10% of the urban population. Today, India is the world’s top exporter of agricultural goods such as the coffee, rice, tea, vegetables, etc. as well as their preparation and marine products. The Agricultural Researching Systems in the India pinnacle of process that began the nineteenth century and culminated in the formation of Indian Councils of Agricultural Research (ICAR) in 1929 recommendation of Royal Commissions on the Agriculture. The present researching systems, the ICAR primarily assists, promotes, and collaborates on research and education in India at the national level. Because farmers strive to feed globe with the limit naturally resourcing, technologically advancement are the critically to futures of farming. The agri tech solution contributes to the overall expansion of sustainable agriculture and food production. Agri-tech startups and disruptive market newcomers are the focus of the funding. Agriculture output increases as a result of new technology, resource input, and economic incentives. Future food-production and handling technological development should be non-polluting, decrease environmental and health risks, and not inspire additional governmental restrictions.